Answer:
The equation becomes
![7x+6 = 10x-12](https://img.qammunity.org/2021/formulas/mathematics/college/6xaqyc6h3xnzwzmgs5o54zrz70vce2fu75.png)
Thus, the number = x = 6
Explanation:
Let 'x' the number
seven times a number = 7x
Six more than seven times a number = 7x+6
10 times the number -12 = 10x-12
Given that Six more than seven times a number equals 10 times the number -12.
Thus, the equation becomes
![7x+6 = 10x-12](https://img.qammunity.org/2021/formulas/mathematics/college/6xaqyc6h3xnzwzmgs5o54zrz70vce2fu75.png)
We can further solve for x
![7x+6 = 10x-12](https://img.qammunity.org/2021/formulas/mathematics/college/6xaqyc6h3xnzwzmgs5o54zrz70vce2fu75.png)
![6+12 = 10x-7x](https://img.qammunity.org/2021/formulas/mathematics/college/60x0gnm0eokw8nhaiy9nwzsp29gd9mnrtb.png)
![18 = 3x](https://img.qammunity.org/2021/formulas/mathematics/middle-school/y39gxusfr8boaseu4hid3dwjwg1worfg7j.png)
![x = 6](https://img.qammunity.org/2021/formulas/mathematics/middle-school/rfxeu0rgxtdic6lqlcq5waa012fmosd2e9.png)
Thus, the number = x = 6